Sosialisasi Menggagas Pemanfaatan Sumber Air Terbatas Untuk Pertanian Di Dusun Tampes Kecamatan Kayangan Kabupaten Lombok Utara: Potensi - Kadek Wiratama; I Nyoman Merdana; I Dewa Gede Jaya Negara (Universitas Mataram, 2022)
Abstract: Water is a necessity for all living things on this earth, and if there is a limited presence of water, especially on dry land, it will be able to limit all life activities around it. Likewise in the North Lombok Regency area, namely in the Tampes Region, the existence of surface water sources is only found in a few locations with very minimal water potential, while the existing water sources are not used for agriculture so that the existing dry land cannot be cultivated or idle. The existence of water potential around settlements has not been able to be utilized to provide economic value by local residents, due to the limited knowledge of the community. To anticipate global climate change, which will impact on decreasing water availability, residents in this dry area must be prepared by providing counseling. The community must gain insight into this matter, and so that the community is able to establish communication with other related parties to help with the difficulties they face. This service is carried out by conducting socialization about the importance of water resources and dry land to improve the family's economy, socialization is carried out at the field level by involving community leaders and residents around the river. The target of the service is the people who live around the river in Tampes hamlet and community leaders. The aim of this outreach is to increase public knowledge about the use of water sources and dry land for agriculture. The socialization is carried out in a sequence of initial survey activities, field reviews, lectures and discussions, which are carried out at the field level with the community. The result achieved is that the residents around the river have gained knowledge about the benefits of existing river water and understand how to use it, able to make ideas that are proposed to the village to be used as village program